2016
DOI: 10.1103/physreva.93.062303
|View full text |Cite
|
Sign up to set email alerts
|

Stark echo modulation for quantum memories

Abstract: Quantum memories for optical and microwave photons provide key functionalities in quantum processing and communications. Here we propose a protocol well adapted to solid state ensemble based memories coupled to cavities. It is called Stark Echo Modulation Memory (SEMM), and allows large storage bandwidths and low noise. This is achieved in a echo like sequence combined with phase shifts induced by small electric fields through the linear Stark effect. We investigated the protocol for rare earth nuclear spins a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 33 publications
0
52
0
Order By: Relevance
“…This can be used to interface microwave photons to a RE doped crystal through a superconducting resonator 22,23 and obtain quantum memories for superconducting qubits. [24][25][26] In this case too, nuclear hyperfine transitions can provide long storage time. We recently showed that 145 Nd 3+ :Y 2 SiO 5 hyperfine transitions have ground state coherence lifetimes up to 9 ms at 5 K, whereas the electron spin T 2 is about 100 µs.…”
Section: -4mentioning
confidence: 99%
“…This can be used to interface microwave photons to a RE doped crystal through a superconducting resonator 22,23 and obtain quantum memories for superconducting qubits. [24][25][26] In this case too, nuclear hyperfine transitions can provide long storage time. We recently showed that 145 Nd 3+ :Y 2 SiO 5 hyperfine transitions have ground state coherence lifetimes up to 9 ms at 5 K, whereas the electron spin T 2 is about 100 µs.…”
Section: -4mentioning
confidence: 99%
“…Recently demonstrated ac Stark modulations in a double rephasing photon echo scheme 23 have exhibited a similar mechanism of atom phase control to dc Stark echoes 12 , 13 , in which the Stark field provides an on-purpose phase shift (turbulence) so that the transient atoms cannot be concurrently rephased for the first echo. As mentioned above, however, ref.…”
Section: Introductionmentioning
confidence: 97%
“…To overcome the population inversion constraint in photon echoes, several modified photon echo schemes have been developed for quantum memory applications since 2001 1 . The modified photon echo schemes for quantum memory protocols include controlled reversible inhomogeneous broadening (CRIB) 1 5 and atomic frequency comb (AFC) echoes 6 9 for a single rephasing scheme, and silent echoes 10 , 11 , dc Stark echoes 12 , 13 , controlled double rephasing (CDR) echoes 14 , 15 and optically locked photon echoes 16 for a double rephaisng scheme. These modified photon echo protocols can also be categorized as two-level 3 , 4 , 6 , 9 13 or three-level 1 , 2 , 5 , 7 , 8 , 14 – 16 schemes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, they can be useful to manipulate spin state because their effect can accumulate over long coherence lifetimes. This has been used to design a low noise and broadband quantum memory protocol that can be used for optical, electron and nuclear spin transitions …”
Section: Materials For Quantum Information Processingmentioning
confidence: 99%